Immunotherapy in Myeloma A Theme Issue in Honor of Prof. Dr. Gösta Gahrton - Kröger, Nicolaus; Garderet, Laurent (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Immunotherapy in multiple myeloma, first investigated with allogeneic stem cell transplantation, is now a major pillar in the treatment of multiple myeloma. CAR-T-cell technology, monoclonal or bispecific antibodies, as well as new forms of cellular therapy, have revolutionized the treatment of this hematological malignancy.